MEDIA SOSIAL SEBAGAI BUDAYA BARU PEMBELAJARAN DI SD MUHAMMADIYAH 9 MALANG - Kamal, Mohammad (Unitri Press, 2020)
This study tries to find answers to the application of social media as a new form of culture in learning. SD Muhammadiyah 9 Malang which is the object of research has characteristics that are in line with the research theme. SD Muhammadiyah 9 Malang has implemented social media in the last few years. In the results of this study found many interesting things that can be said as a form of habit which in social language is called culture. In addition, the impact of this new learning culture is very positive. This means it is different from the previous community's understanding that social media must be kept away from children because it can interfere with learning. From the application of social media for learning, SD Muhammadiyah 9 Malang can encourage students to be creative, innovative and able to adapt critically to the negative effects of social media. Although there are some notes that need attention or just tips and tricks from teachers or teachers to avoid the negative impact of social media.